Speech rehabilitation of Paradoxical Vocal Fold Movement - Shobha Sharma,; Baljit Kaur Hardial Singh, (penerbit ukm, 2007)
Many forms of management of the Paradoxical Vocal Fold Movement (PVFM) disorder have been presented in past literature, but it is vital to recognize the complexity of the disorder and the necessity for proper diagnosis to allow for appropriate management. A review of the literature suggests that this disorder predominantly occurs in the young female, and presents with a history of associated medical conditions. A single case study of an unusual presentation of PVFM in a young eleven year old boy with PVFM is discussed in this paper. The PVFM was observed and diagnosed by the Otorhinolaryngologist at the University Malaya Medical Center (UMMC), Kuala Lumpur. Nasendoscopy revealed otherwise normal vocal fold movement in quiet breathing and during Jurnal Sains Kesihatan Malaysia 5 (1) 2007: 67-7868 an episodic attack. The young boy was subsequently referred for speech therapy; management of the PVFM was solely with speech rehabilitation. The management of the disorder in this young boy is discussed up to the time of discharge from therapy.